Diversity of Free-Living and Particle-Attached Prokaryotes in a River-Influenced Coastal Area of the Northern Adriatic Sea - Trano, Anna Chiara; Piredda, Roberta; Balestra, Cecilia; Bastianini, Mauro; Gasol, Josep M.; Casotti, Raffaella (Frontiers in Marine Science, 2022)
The Northern Adriatic Sea is a key area of the Mediterranean Sea, strongly affected by freshwater inputs, mainly from the Po River, which bring high amounts of nutrients as well as organic and inorganic particles. Free-living and particle-attached prokaryotes were characterized by 16S rRNA gene amplicon sequencing of size-fractionated samples collected during a diatom bloom in this area. The diversity of free-living and particle-attached prokaryotic assemblages was investigated with the aim to understand how the microbial communities are structured in the two fractions and whether specific microbial groups are associated to one lifestyle or the other. The results highlight a diverse prokaryotic community dominated by Proteobacteria, Bacteroidetes, and, remarkably, Firmicutes. Taxa within Firmicutes and Alphaproteobacteria are identified as the main particle-attached indicators by LEfSe, while members of Bacteroidetes and Gammaproteobacteria were representative of the free-living lifestyle, although they were also usually found as particle-attached. Collectively, the results suggest that both the free-living and the particle-attached lifestyles are a complex combination of specialization and adaptation to local conditions.